Colonial Cities in Motion Urban Symbolism and Popular Radicalism - Abidin Kusno (HISKI, 2008)
This paper concems with the change in the visual environment of colonial city and the ways in which they helped to shape political imagination. What kinds of architectural and urban spectacles were constructed and what role did they play in contributing to the formation of alternative identities for the Indonesians under Dutch colonial rule? How could colonial cities be understood less as a